Differential responses of canonical nitrifiers and comammox Nitrospira to long-term fertilization in an Alfisol of Northeast China - Wang, Yanan; Zeng, Xibai; Ma, Qiang; Zhang, Yang; Yu, Wantai; Zheng, Zhong; Zhang, Nan; Xu, Liyang (Frontiers in Microbiology, 2023)
The newly identified complete ammonia oxidizer (comammox) that converts ammonia directly into nitrate has redefined the long-held paradigm of two-step nitrification mediated by two distinct groups of nitrifiers. However, exploration of the niche differentiation of canonical nitrifiers and comammox Nitrospira and their ecological importance in agroecosystems is still limited. Here, we adopted quantitative PCR (qPCR) and Illumina MiSeq sequencing to investigate the effects of five long-term fertilization regimes in the variations of ammonia-oxidizing bacteria (AOB), ammonia-oxidizing archaea (AOA), nitrite-oxidizing bacteria (NOB) and comammox Nitrospira abundances and comammox community composition in two soil layers (0-20 cm, topsoil; 20-40 cm, subsoil) in an Alfisol in Northeast China. The fertilization treatments included no fertilizer (CK); chemical nitrogen (N) fertilizer; chemical N; phosphorus (P) and potassium (K) fertilizers (NPK); recycled organic manure (M) and chemical N, P, K plus recycled manure (MNPK). Compared with CK, manure and/or chemical fertilizer significantly increased the AOB amoA gene abundance. Long-term recycled manure increased soil organic matter (SOM) contents and maintained the soil pH, but decreased the NH4+-N concentrations, which markedly promoted the nxrA and nxrB gene abundances of NOB and the amoA gene abundances of comammox Nitrospira clade A and AOA. Although the comammox Nitrospira clade B abundance tended to decrease after fertilization, the structural equation modeling analysis showed that comammox clade B had direct positive impacts on soil potential ammonia oxidation (PAO) (λ=0.59, P<0.001). The long-term fertilization regime altered the community composition of comammox Nitrospira. Additionally, comammox Nitrospira clades A and B had individual response patterns to the soil layer. The relative abundance of clade A was predominant in the topsoil in the N (86.5%) and MNPK (76.4%) treatments, while clade B appeared to be dominant in the subsoil (from 78.7% to 88.1%) with lower ammonium contents, implying niche separation between these clades. Soil pH, NH4+-N and SOM content were crucial factors shaping the soil nitrifying microbial abundances and the comammox Nitrospira community. Together, these findings expand the current understanding of the niche specialization and the important role of comammox Nitrospira in terrestrial ecosystems.